2018
DOI: 10.1016/j.otsr.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction with the Tape Locking Screw (TLS) and a short hamstring graft: Clinical evaluation of 61 cases with a minimum 12 months’ follow-up

Abstract: IV, prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…During the first phase (between preoperative and M1) Δ L and Δ C decrease significantly, then during the second phase (between M1 and M9) Δ L and Δ C gradually increase, and during the third phase (between M9 and last FU) Δ L and Δ C stabilise. At the last FU, mean Δ L was close to 1 mm (range 0–2.8 mm) at all force‐levels, which is consistent with other series [12, 29, 34, 41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During the first phase (between preoperative and M1) Δ L and Δ C decrease significantly, then during the second phase (between M1 and M9) Δ L and Δ C gradually increase, and during the third phase (between M9 and last FU) Δ L and Δ C stabilise. At the last FU, mean Δ L was close to 1 mm (range 0–2.8 mm) at all force‐levels, which is consistent with other series [12, 29, 34, 41].…”
Section: Discussionsupporting
confidence: 90%
“…Many studies that have objectively evaluated knee joint laxity (“laximetry”) suggest that a greater measurement is associated with greater intra‐articular pathology (meniscal and/or ligamentous lesions) [3, 21, 35]. Some have used laximetry to compare different types of grafts [4], or as a means of postoperative outcome evaluation [29, 42]. There are, however, few studies that have focused on the evolvement of knee joint laxity during the first postoperative year [15, 38].…”
Section: Introductionmentioning
confidence: 99%
“…Another alternative is using a single bundle four-strand semitendinosus tendon graft (ST4), fixed to a femoral and tibial socket through an “all inside technique” (AIT) [ 3 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The potential advantages of AIT include preservation of bone stock, reduced incidence of complications (tibial plateau fractures, decreased cortical bone periosteal disruption, decreased postoperative pain), improved bone–graft integration, accelerated graft maturation, increased precision of anatomic placement [ 11 , 14 , 15 , 16 ], and, usually, an ST4 graft harvest with a larger diameter graft [ 5 , 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We describe this technique as a short graft with tape suspension (SGTS). The proposed benefits of this technique include requiring only a single hamstring tendon which can be passed through smaller bone tunnels [9] . It has also been suggested that the dedicated interference screw gains better traction against the PET strip compared to soft tissue graft, which may reduce slippage of the graft-tape construct [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Very little slippage has been shown between the tape and screw fixation in comparison to other devices [24]. Finally, the graft is pretensioned with 500N for 1-2 minutes, theoretically minimising further elongation of the graft after implantation [6, 23].…”
Section: Introductionmentioning
confidence: 99%